(untitled) (American Journal of Islam and Society, 2016)
What if someone wrote an introduction to Islam that was “not Sunnī-centered, or male-centered, or law-centered” (p. 4)? What if it did not focus on a theoretical Arab Muslim heartland and “let only the classical male theologians and jurists speak” (p. 4)? And what if “magic became the primary lens that informed the author’s priorities” (p. 4)? Magic in Islam is what would happen. Through “magic,” Knight pokes holes in narratives about Islam held by Muslims (such as the notion of a monolithic, static Islamic orthodoxy) and the general populace (such as the “clash of civilizations” narrative). Title aside, Magic in Islam is really about American Islam, not magic; that is, it implicitly compares Islam’s esoteric heritage with the dry, hyper-logical brand of Islam popular in American MSAs and at ISNA, as well as “Protestant-ish” assumptions about Islam in the broader American discourse. Knight presents himself as neither a specialist in nor a practitioner of the esoteric, and readers expecting a catalogue of Muslim occult practices will be disappointed (and perhaps enraged). Instead, he acts as a wide-eyed observer guiding the reader through the curiosities of Muslim heritage. Knight did not invent this genre, nor is his main contribution in presenting original research. Rather, his main contribution is in making abstruse academic texts meaningful to the non-specialist, and in a way that is engaging and fun. From this angle, Magic in Islam is similar to his other projects, such as The Taqwacores (2004) and Journey to the End of Islam (2009). However, while his writing here is still playfully irreverent, it is considerably toned down, with only an infrequent swear word or allusion to an indelicate act. Hence, despite its potentially heterodox subject, it is more likely to agree with conservative sensibilities. Ironically, it is also far more grounded in orthodoxy. While Knight proposes to “let the intro come through marginalized voices” (p. 4), particularly loud voices include those of orthodox giants such as al-Bukhari and Ahmad ibn Hanbal, as well as less-orthodox but still mainstream-enough voices such as those of al-Kindi and Ibn al-‘Arabi. (This is in contrast to truly marginalized voices, such as those of amulet sellers, jinn exorcists, or women.) Nonetheless, the writing is mature and thoughtful, and I would be comfortable using it as a supplementary textbook in an “Introduction to Islam” class ...